IMPROVING VOCATIONAL STUDENTS’ SPEAKING SKILL THROUGH ROLE PLAY TECHNIQUE - Nurdiana Mahdalena Sinurat; Willem Saragih (Universitas Negeri Medan, 2014)
This study was attempted to improve vocational students’ speaking skill throughRole Play Technique. This study was conducted by using classroom actionresearch. The subject of the research was class XI EK 2 SMK Negeri 1 Merdeka,Berastagi, consists of 21 students. This research was conducted in two cycles. Theinstruments of collecting data were diary notes, observation sheet, questionnairesheet, interview sheet and tests. Based on the speaking test score, it was found thatthe students’ score kept improving from the first test to the third test. In theorientation test, the mean score was 37.66, in the first cycle test, the mean scorewas 48.33, and in the second cycle test, the mean score was 57.33. There wasimprovement of students’ achievement from 57.33-37.66 about 19.67 points.Based on the data from diary notes, observation sheet, questionnaire sheet andinterview, it was found that the students agreed that Role Play technique helped toencourage them to speak, to express the language through appropriateexpressions, to think that speaking is not difficult. Thus, it was found thatteaching-learning process ran well. Students were active and interested inspeaking in the classroom. The result of the research shows that Role PlayTechnique can improve vocational students’ speaking skill.